2021
DOI: 10.1186/s12651-021-00305-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effect of gender segregation on the gender gap in time-related underemployment

Abstract: This paper focuses on the impact that gender segregation in the labour market exerts on the underemployment gender gap for young adult workers in Spain. In order to analyse the relative importance of segregation in this gap, we develop a methodology based on two counterfactual simulations that provides a detailed decomposition of the gap into endowments and coefficients effects as well as the interaction of these effects. To the best of our knowledge, we are the first to perform a decomposition using bivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…For example, women, especially women with children, are required to find a new job more quickly than men after leaving their jobs. There are several studies that found higher rates of underemployment among women (e.g., Acosta-Ballesteros et al, 2021;Jefferson & Preston, 2010;Jensen & Slack, 2003;Kamerade & Richardson, 2017;Mau & Kopischke, 2001). The fact that women concentrate on jobs which are usually part-time and low-paid and men get jobs which produce better rewards for similar qualifications is argued to be the main driver behind this pattern (Acosta-Ballesteros et al, 2021;Kamerade & Richardson, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, women, especially women with children, are required to find a new job more quickly than men after leaving their jobs. There are several studies that found higher rates of underemployment among women (e.g., Acosta-Ballesteros et al, 2021;Jefferson & Preston, 2010;Jensen & Slack, 2003;Kamerade & Richardson, 2017;Mau & Kopischke, 2001). The fact that women concentrate on jobs which are usually part-time and low-paid and men get jobs which produce better rewards for similar qualifications is argued to be the main driver behind this pattern (Acosta-Ballesteros et al, 2021;Kamerade & Richardson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that found higher rates of underemployment among women (e.g., Acosta-Ballesteros et al, 2021;Jefferson & Preston, 2010;Jensen & Slack, 2003;Kamerade & Richardson, 2017;Mau & Kopischke, 2001). The fact that women concentrate on jobs which are usually part-time and low-paid and men get jobs which produce better rewards for similar qualifications is argued to be the main driver behind this pattern (Acosta-Ballesteros et al, 2021;Kamerade & Richardson, 2017). However, McKee-Ryan & Harvey (2011) pointed out that there are studies showing no relationship between sex and underemployment, such as in the USA, Belgium, England, Italy, Portugal, Spain and the Netherlands, or there are also studies showing higher underemployment rates for men such as in Portugal, the USA, Canada and the UK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation